Anoxygenic photosynthesis linked to Neoarchean iron formations in Carajás (Brazil). Issue 4 (4th March 2021) - Rego, Eric Siciliano; Busigny, Vincent; Lalonde, Stefan V.; Philippot, Pascal; Bouyon, Amaury; Rossignol, Camille; Babinski, Marly; de Cássia Zapparoli, Adriana
Abstract: Microbial activity is often invoked as a direct or indirect contributor to the precipitation of ancient chemical sedimentary rocks such as Precambrian iron formations (IFs). Determining a specific metabolic pathway from the geological record remains a challenge, however, due to a lack of constraints on the initial conditions and microbially induced redox reactions involved in the formation of iron oxides. Thus, there is ongoing debate concerning the role of photoferrotrophy, that is the process by which inorganic carbon is fixed into organic matter using light as an energy source and Fe(II) as an electron donor, in the deposition of IFs. Here, we examine 2.74‐Ga‐old Neoarchean IFs and associated carbonates from the Carajás Mineral Province, Brazil, to reconstruct redox conditions and to infer the oxidizing mechanism that allowed one of the world's largest iron deposits to form. The absence of cerium (Ce) anomalies reveals that conditions were pervasively anoxic during IF deposition, while unprecedented europium (Eu) anomalies imply that Fe was supplied by intense hydrothermal activity. A positive and homogeneous Fe isotopic signal in space and time in these IFs indicates a low degree of partial oxidation of Fe(II), which, combined with the presence of 13 C‐depleted organic matter, points to a photoautotrophic metabolic driver. Collectively, our results argue in favor of reducing conditions during IF deposition and suggest anoxygenic photosynthesis as the most plausible mechanism responsible for Fe oxidation in the Carajás Basin.